Human Infection with Rickettsia felis, Kenya - Richards, Allen L. (Centers for Disease Control and Prevention, 2010)
To determine the cause of acute febrile illnesses other than malaria in the North Eastern Province, Kenya, we investigated rickettsial infection among patients from Garissa Provincial Hospital for 23 months during 2006–2008. Nucleic acid preparations of serum from 6 (3.7%) of 163 patients were positive for rickettsial DNA as determined by a genus-specific quantitative real-time PCR and were subsequently confirmed by molecular sequencing to be positive for Rickettsia felis. The 6 febrile patients’ symptoms included headache; nausea; and muscle, back, and joint pain. None of the patients had a skin rash.